2020
DOI: 10.1126/sciadv.abb3713
|View full text |Cite
|
Sign up to set email alerts
|

GADL1 is a multifunctional decarboxylase with tissue-specific roles in β-alanine and carnosine production

Abstract: Carnosine and related β-alanine–containing peptides are believed to be important antioxidants, pH buffers, and neuromodulators. However, their biosynthetic routes and therapeutic potential are still being debated. This study describes the first animal model lacking the enzyme glutamic acid decarboxylase–like 1 (GADL1). We show that Gadl1−/− mice are deficient in β-alanine, carnosine, and anserine, particularly in the olfactory bulb, cerebral cortex, and skeletal muscle. Gadl1−/− mice also exhibited decreased a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 84 publications
2
32
0
Order By: Relevance
“…Another candidate region on the BTA22 (at position: 4,790,000-6,620,000 bp) identified by the XP-EHH IND versus North AFT test harboured four genes (GADL1, TGFBR2, STT3B and OSBPL10) and among these, GADL1 gene is one of the genes involved in adaptive evolution of Anolis carolinensis introduced into the Ogasawara archipelago 43 . Gadl1 −/− mice exhibited www.nature.com/scientificreports/ decreased anxiety, increased levels of oxidative stress markers, alterations in energy and lipid metabolism, and age-related changes 44 . STT3B is a catalytic subunit of hetero oligomeric oligosaccharyltransferase (OST), which is important for asparagine linked glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate region on the BTA22 (at position: 4,790,000-6,620,000 bp) identified by the XP-EHH IND versus North AFT test harboured four genes (GADL1, TGFBR2, STT3B and OSBPL10) and among these, GADL1 gene is one of the genes involved in adaptive evolution of Anolis carolinensis introduced into the Ogasawara archipelago 43 . Gadl1 −/− mice exhibited www.nature.com/scientificreports/ decreased anxiety, increased levels of oxidative stress markers, alterations in energy and lipid metabolism, and age-related changes 44 . STT3B is a catalytic subunit of hetero oligomeric oligosaccharyltransferase (OST), which is important for asparagine linked glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of acidic amino acid decarboxylase GADL1 isoform X1 ( GADL1 ), which is involved with β-alanine metabolism in chicken, was detected in the L-histidine supplementation group. GADL1 is considered to be an enzyme with multiple biological activities and is responsible for converting aspartic acid to β-alanine in carnosine biosynthesis [ 25 ]. In mice, GADL1 knockout mice were deficient in β-alanine and carnosine in the skeletal muscle [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…GADL1 is considered to be an enzyme with multiple biological activities and is responsible for converting aspartic acid to β-alanine in carnosine biosynthesis [ 25 ]. In mice, GADL1 knockout mice were deficient in β-alanine and carnosine in the skeletal muscle [ 25 ]. However, the association of the GADL1 and carnosine contents has not been reported in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified GADL1 as novel and abundantly expressed hair cell marker, and in this present study, we found it only in mature hair cells (FC = 2224, FDR = 2.5 × 10 −50 ). GADL1 decarboxylates amino acids and is important for the biosynthesis of taurine (Liu et al, 2012; Mahootchi et al, 2020), which modulates intracellular calcium homeostasis in the cochlea (Liu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…decarboxylates amino acids and is important for the biosynthesis of taurine (Liu et al, 2012;Mahootchi et al, 2020), which modulates intracellular calcium homeostasis in the cochlea (Liu et al, 2006).…”
Section: Biophysical Properties Of Mature Hair Cells Can Be Inferred By Comparison To Young Hair Cellsmentioning
confidence: 99%